Pedagogical Strategies for Character Building in Islamic Education: Addressing Moral Degradation in Secondary Schools - Marzuki Yusuf; Jaenullah Jaenullah; M. Saidun Anwar; Rizky Hidayatullah; Subandi Subandi; Apri Wahyudi (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to analyze the pedagogical strategies employed by Islamic Religious Education (PAI) teachers in building noble character (akhlakul karimah) among students at SMA Riyadlul Ulum Sukoharjo, North Lampung, as a response to the growing phenomenon of moral degradation among adolescents. Utilizing a qualitative descriptive approach with a phenomenological design, data were collected through participatory observation, in-depth interviews with the principal and PAI teachers, and documentation study. The findings reveal an integrated implementation of five core instructional strategies: (1) direct instruction through interactive lectures and role modeling; (2) indirect instruction via religious culture habituation; (3) interactive instruction through reflective group discussions; (4) independent study using daily moral journals; and (5) experiential learning through social activities and student organizations. These strategies effectively fostered discipline, honesty, and responsibility, supported by a strong school culture, although social media remained a primary inhibiting factor. The study concludes that the synergy of these five pedagogical approaches provides a holistic framework for internalizing moral values, transforming them from abstract concepts into daily behavioral habits. These results imply that character building in secondary schools requires a collaborative ecosystem between structured teaching, personal reflection, and real-world practice to effectively address modern moral challenges.